Overview of Ground-Motion Issues for Cascadia Megathrust Events: Simulation of Ground-Motions and Earthquake Site Response - Ghofrani, Hadi; Atkinson, Gail M.; Molnar, Sheri (Frontiers in Built Environment, 2017)
Ground motions for earthquakes of M7.5 to 9.0 on the Cascadia subduction interface are simulated based on a stochastic finite-fault model and used to estimate average response spectra for reference firm soil conditions. The simulations are first validated by modeling the wealth of ground-motion data from the 2011 M9.0 Tohoku earthquake of Japan. Adjustments to the calibrated model are then made to consider average source, attenuation and site parameters for the Cascadia region. This includes an evaluation of the likely variability in stress drop for large interface earthquakes and an assessment of regional attenuation and site effects. We perform best-estimate simulations for a preferred set of input parameters. Typical results suggest mean values of 5%-damped pseudoacceleration in the range from about 100 to 200 cm/s2, at frequencies from 1 to 4 Hz, for firm-ground conditions in Vancouver. Uncertainty in most-likely value of the parameter representing stress drop causes variability in simulated response spectra of about ±50%. Uncertainties in the attenuation model produce even larger variability in response spectral amplitudes—a factor of about two at a closest distance to the rupture plane (Rcd) of 100 km, becoming even larger at greater distances. It is thus important to establish the regional attenuation model for ground-motion simulations and to bound the source properties controlling radiation of ground motion. We calculate theoretical one-dimensional spectral amplification estimates for four selected Fraser River Delta sites to show how the presence of softer sediments in the region may alter the predicted ground motions. The amplification functions are largely consistent with observed spectral amplification at Fraser River delta sites, suggesting amplification by factors of 2.5–5 at the peak frequency of the site; we note that deep sites in the delta have a low peak frequency, ∼0.3 Hz. This work will aid in seismic hazard assessment and mitigation efforts in the active Cascadia region of southwestern BC. An important consideration is that the uncertainties are large and present a dominant unknown when assessing seismic risk. We find that variability in the expected motions exceeds a factor of two even on rock-like sites, with uncertainty in site response further increasing this factor. Such large uncertainties pose a major challenge in preparing for the potential consequences of the next megathrust event in Cascadia.